ANALYSIS OF BUSINESS COMPETITION ON THE SALES OF LAMONGAN SPECIAL FOOD (STUDY ON BORAN RICE TRADERS IN LAMONGAN) - Ahmad Yani Syaikhudin (Jurnal Inovasi Penelitian, 2021)
There are two factors that influence purchasing decisions. These factors include internal factors and external factors. Internal factors include perceptions, attitudes, lifestyle and personality, while external factors include culture, social, reference and family. Product factors, economic factors, psychological factors, and sociological factors that generally determine a person's behavior. A number of experts stated the magnitude of the influence of the above factors on consumer behavior, social class factors, family, style, life, personality, self-ability, perception, and learning, which are consumer attitudes in making purchases. To understand consumer behavior, business people will be able to understand what needs consumers want, which can then be used to follow up in making the right marketing decisions, or to find out whether or not there are new opportunities that come from not being fulfilled a need. The need to understand consumer behavior is based on the factors that influence the consumer's decision-making process to buy a product. Meanwhile, consumer decisions are influenced by various factors, one of which is internal factors and external factors. Internal factors (X1) affect the purchase decision for boran rice in Lamongan. Then the purchase decision will increase further, this shows that hypothesis 1 is accepted. External factors (X2) affect the purchase decision for boran rice in Lamongan. Then the decision to buy boran rice will increase further, this shows that hypothesis 2 is accepted. It can be concluded that internal and external factors have an influence on purchasing decisions for boran rice, but internal factors have the most dominant influence on purchasing decisions for boran rice in Lamongan. This shows that hypothesis three is accepted.